2022
DOI: 10.3390/bioengineering9040133
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Processing Potential of Ethiopian Agricultural Residue Enset/Ensete ventricosum for Biobutanol Production

Abstract: The Enset plant is a potential food source for about 20 million Ethiopians. A massive amount of residual byproduct is discarded from traditional Ethiopian Enset food processing. This study shows a compositional analysis of Enset biomass and its use for biobutanol production. The Enset biomass was pretreated with 2% (w/v) NaOH or 2% (v/v) H2SO4 and subjected to enzymatic hydrolysis. The enzymatic hydrolysates were then fermented anaerobically by C. saccharoperbutylacetonicum DSM 14923. The majority of Enset bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…This could be due to the structural difference of the lignocellulosic biomass. Studies showed that Enset ber has lower lignin and higher cellulose content than wheat straw [5], which could make Enset ber a more suitable substrate for the fungi. Geoffrey L. et al [29] conducted experiments in order to determine whether lignin is degraded by ruminal fungi, Neocallimastix sp.…”
Section: Anaerobic Fungal Growth On Enset Bermentioning
confidence: 99%
See 2 more Smart Citations
“…This could be due to the structural difference of the lignocellulosic biomass. Studies showed that Enset ber has lower lignin and higher cellulose content than wheat straw [5], which could make Enset ber a more suitable substrate for the fungi. Geoffrey L. et al [29] conducted experiments in order to determine whether lignin is degraded by ruminal fungi, Neocallimastix sp.…”
Section: Anaerobic Fungal Growth On Enset Bermentioning
confidence: 99%
“…An enormous amount of byproduct known as Enset biomass is thrown away during traditional Ethiopian Enset food processing. A major source of cellulose from the Enset plant is the Enset ber, midrib, and leaf sheath peel, which contain 67.1%, 40%, and 34.1% cellulose, respectively [5]. Recent studies have shown that Enset biomass is a very promising lignocellulosic biomass for biobutanol [5] and pulp [6] production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hemicellulose in the bers is mostly highly acetylated xylanes ranging from 15.6-27.6%. [1][2][3][4] The high cellulose and low lignin content of Enset ber promotes its utilization for the production of dissolving pulp.…”
Section: Introductionmentioning
confidence: 99%
“…Bulla, Kocho, and Amicho are three foods made from the crop that are excellent sources of starch and carbohydrates (Olango et al, 2014a;Yemataw et al, 2018). Additionally, this plant is an excellent source of ber and animal feed (Seid et al, 2022). Enset can be grown in a much larger area to feed more than 100 million people and improve food security in Ethiopia, Kenya, Uganda, and Rwanda, according to recent modeling studies.…”
Section: Introductionmentioning
confidence: 99%